Responding to an Increased Minimum Wage: A Mixed Methods Study of Child Care Businesses during the Implementation of Seattle's Minimum Wage Ordinance - Jennifer J. Otten; Katherine Getts; Anne Althauser; James Buszkiewicz; Ekaterina Jardim; Heather D. Hill; Jennifer Romich; Scott W. Allard (Social Work and Society)
Low wages are a persistent feature of child care jobs and affect the quality of children's care in the U.S. In this article, we examine how implementation of Seattle's minimum wage law affected the local child care sector using three datasets: (1) state administrative records on approximately 200 Seattle-based child care businesses; (2) a longitudinal employer survey of 41 child care centers; and (3) in-depth interviews of 15 Seattle child care center directors. Findings suggest that initial increases in the local minimum wage affected the majority of child care businesses. Providers' most commonly responded to higher labor costs by raising tuition and reducing staff hours or headcount"”strategies that may negatively impact low-income families and staff. While raising wages may help some child care employees, considering the full range of effects of this policy underscores the need for a systems approach to supporting the child care sector as a whole.